Distinct infectivity and neutralization antibody responses in the highly homologous AAV Go.1 and AAV5 - Li, Mei; Ma, Haixiao; Wu, Yang; Gao, Yunling; Wang, Jie; Wang, Hanbing (Frontiers in Medicine, 2025)
IntroductionGoat-derived adeno-associated virus (AAV) vectors, such as AAV Go.1, represent a novel platform for gene therapy due to their unique origin and potential advantages in transduction efficiency and immune evasion. However, their therapeutic potential and biological properties remain underexplored.MethodsIn this study, we developed a recombinant AAV (rAAV) Go.1 by replacing the goat AAV rep gene with the standard AAV2-rep gene to improve packaging efficiency. We compared the transduction efficiency of rAAV Go.1 with that of AAV5, a closely related serotype with 95% genome similarity, both in vitro and in vivo. Additionally, we assessed immune evasion properties by evaluating resistance to neutralization using sera from rAAV5-immunized mice and human volunteers. To further enhance transduction efficiency, we introduced site-specific mutations in the VP1 unique (VP1u) region and VP1/2 common region.ResultsThe rep gene modification led to a significantly higher packaging efficiency for rAAV Go.1 compared to the original goat AAV. rAAV Go.1 exhibited markedly higher transduction efficiency than AAV5 in both in vitro and in vivo models. Furthermore, rAAV Go.1 demonstrated a 4-fold increase in resistance to neutralization by sera from rAAV5-immunized mice. A study involving 20 healthy volunteers revealed that high-titer neutralizing antibodies had a more pronounced inhibitory effect on rAAV5 compared to rAAV Go.1. Mutagenesis studies identified key modifications that enhanced viral properties: K32R, K91R, and K122R mutations in the VP1u region significantly improved viral production, while K137R (VP1u) enhanced transduction efficiency in vitro and in vivo.DiscussionOur findings highlight the potential of rAAV Go.1 as an improved gene therapy vector with superior transduction efficiency and enhanced immune evasion. The identified VP1 mutations further optimize viral properties, making rAAV Go.1 a promising candidate for future therapeutic applications.